REPRESENTASI EKSPLOITASI TERHADAP MASYARAKAT DALAM NOVEL TERUSLAH BODOH JANGAN PINTAR KARYA TERE LIYE TINJAUAN MARXISME - Miranda Miranda; Elsa Mulya Karlina (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the forms of community resistance against exploitation depicted in the novel Teruslah Bodoh Jangan Pintar by Tere Liye. The exploitation carried out by the authorities in this novel is depicted as very systematic, structured, and detrimental to the lower classes both economically, socially, and psychologically. However, the community is not only depicted as the oppressed or resigned party, but as an active and conscious subject in resisting the injustice they experience. This study uses a sociological literary approach with a qualitative descriptive method, namely by analyzing literary texts based on the social reality reflected in them. The results of the analysis show that the forms of community resistance in this novel are manifested in various ways, such as collective awareness of oppression, the courage to speak the truth, open criticism of an unequal system, and social solidarity between citizens. This resistance represents the struggle of the lower class in facing an exploitative and inhumane system. Through this depiction, Tere Liye conveys sharp social criticism and raises readers' awareness of the importance of the role of society in fighting for social justice. Thus, this novel not only has aesthetic value, but also an educational and reflective function on the social conditions of today's society.